Preferensi Peternak terhadap Bangsa Ternak Sapi Potong Rakyat: Studi Kasus di Desa Benus Kecamatan Naibenu Kabupaten Timor Tengah Utara - Seran, Maria Metriana; Sahala, Josua; Banu, Marselinus; Neonnub, Jefrianus; Mau, Sisilia Fransiska; Bria, Delfan Amelia; Sikone, Alexander (JURNAL RISET RUMPUN ILMU HEWANI, 2026)
The purpose of this study was to determine the characteristics of livestock farmers and analyze livestock farmers' preferences for the breed of beef cattle raised in Benus Village, Naibenu District, TTU Regency. This study employed a survey method. The research location determination technique used a purposive technique (intentionally) with Benus Village as the village with the highest beef cattle population in Benus District, North Central Timor Regency. The sample of livestock farmers consisted of 60 farmers. The research data consisted of primary and secondary data. Data analysis was descriptive quantitative. The results of the study showed that the majority of livestock farmers were 18-64 years old (83%), male farmers (56.67%), the highest level of education was elementary school (55%), all farmers had their own livestock ownership status (100%), the dominant livestock ownership was 1-4 heads, with the majority of farmers also working as farmers (57%), 90% of farmers had livestock farming experience of more than 1-10 years, the largest number of family dependents was 4-6 people (61.67). The type of beef cattle raised is Bali cattle (100%), breeders prefer female cattle (68%), the age of adult female cattle is 2-4 years (40%), the dominant coat color is brick red and white (76.67%), and the body weight is medium (61.67%). The conclusion of this study is that there is a need for improvements in the characteristics of breeders in the form of training and breeder preferences can be used as a guideline in increasing the number of beef cattle populations.